2018
DOI: 10.3390/ijms19123746
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Populus deltoides Leaf Extract via Modulating NF-κB and p38/JNK Pathways

Abstract: Populus deltoides, known as eastern cottonwood, has been commonly used as a medicinal plant. The aim of the present study was to investigate the mechanism underlying the anti-inflammatory activity of P. deltoides leaf extract (PLE). PLE effectively inhibited the expression of inducible nitric oxide synthase (iNOS) and nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells, but not that of cyclooxygenase-2 (COX-2) and prostaglandin E2. Proinflammatory tumor necrosis factor alpha (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…The expression of COX-2, which catalyzes the production of prostaglandins, has also been implicated in inflammation [25]; however, in this experiment, CHE had no effect on COX-2 expression. Similar effects have been reported for the herbal formula SC-E1 and extract of Populus deltoides [26,27].…”
Section: Discussionsupporting
confidence: 85%
“…The expression of COX-2, which catalyzes the production of prostaglandins, has also been implicated in inflammation [25]; however, in this experiment, CHE had no effect on COX-2 expression. Similar effects have been reported for the herbal formula SC-E1 and extract of Populus deltoides [26,27].…”
Section: Discussionsupporting
confidence: 85%
“…During the inflammatory process, the activation of MAPKs family, including extracellular signal-regulated kinases ½ (ERK½), c-Jun amino (N)-terminal kinases (JNK), and p38 MAPK, also plays an essential modulatory role in the adaption and initiation of the transcription of inflammation mediators [ 24 ]. Western blot analyses demonstrated that LPS stimulation activated the phosphorylation of ERK½, JNK, and p38 MAPK, whereas their phosphorylation was effectively suppressed upon pretreatment with Ls-ME ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Following stimulation of macrophages with LPS, the phosphorylation of the IKK complex (IKKα and IKKβ) results in the phosphorylation and degradation of IκBα, thereby promoting the nuclear translocation of NF-κB [34]. The inducible transcription factor NF-κB subsequently activates the LPS-induced inflammatory gene expression in macrophages [35].…”
Section: Resultsmentioning
confidence: 99%